Tantangan Etika Dan Keamanan Dalam Pemanfaatan Teknologi Informasi di Era Digital - Sitorus, Awie Alpany Br; Risya, Neng; Nurbaiti, Nurbaiti (Jurnal Sains, Teknologi & Komputer, 2025)
This study aims to comprehensively examine the ethical and security challenges in the use of information technology in the rapidly evolving digital era. The method used is descriptive qualitative with a literature study approach through the search and analysis of various scientific sources, including national and international journal articles, academic books, official government reports, and data from the Indonesian Internet Service Providers Association for the period 2020 to 2025. Data were analyzed using the Miles and Huberman model which includes the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the increase in digital activity is not balanced by adequate digital literacy and ethical awareness, thus triggering various ethical violations and cybersecurity threats such as data misuse and digital crime. This study confirms that strengthening digital literacy, education on the ethics of technology use, and the consistent implementation of data protection regulations are strategic steps to create a safe and ethical digital ecosystem.